Bioactivity of Humic Acids Extracted From Shale Ore: Molecular Characterization and Structure-Activity Relationship With Tomato Plant Yield Under Nutritional Stress - Monda, Hiarhi; McKenna, Amy M.; Fountain, Ryan; Lamar, Richard T. (Frontiers in Plant Science, 2021)
The increasing demands for biostimulants in the agricultural market over the last years have posed the problem of regulating this product category by requiring the industry to make available the information that demonstrates efficacy and safety, including the explanation of the mode of action and the definition of bioactive constituents. In the present study, we tested the biostimulant proprieties of a sedimentary shale ore-extracted humic acid (HA) on Micro-Tom tomato plants under increasing nutritional stress and investigated the correlation with the chemical features of HA by means of ultra-high resolution FT-ICR MS, FT-ATR and 13C-NMR. Humic acid application proved effective in alleviating nutritional stress by improving nutrient use efficiency, with results comparable to the control treatment supplied with higher NPK nutrition. Increased yield (up to +19%) and fruit quality (in the range +10% -24%), higher ascorbic acid content and a better root growth were the main parameters affected by HA application. Molecular-level characterization identified the possible chemical drivers of bioactivity and included flavonoids, quinones, and alkaloids among the most represented molecules, some of which exhibit antioxidant, pro-oxidant, and antimicrobial activity. The redox effect was discussed as a determinant of the delicate homeostasis balance, capable of triggering plant defense response and eventually inducing a protective priming effect on the plants.